2015
DOI: 10.1021/acs.langmuir.5b01637
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight into Growth Mechanism and Kinetics of Mesoporous Silica Nanoparticles by in Situ Small Angle X-ray Scattering

Abstract: The growth mechanism and kinetics of mesoporous silica nanoparticles (MSNs) were investigated for the first time by using a synchrotron time-resolved small-angle X-ray scattering (SAXS) analysis. The synchrotron SAXS offers unsurpassed time resolution and the ability to detect structural changes of nanometer sized objects, which are beneficial for the understanding of the growth mechanism of small MSNs (∼20 nm). The Porod invariant was used to quantify the conversion of tetraethyl orthosilicate (TEOS) in silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 56 publications
2
63
0
Order By: Relevance
“…The XRD pattern, reported in Figure 2, showed a more defined peak related to the (100) diffraction plane and two broader and less intense peaks assigned to (110) and (200) planes usually attributed to 2D hexagonal pore array (P6 mm symmetry). The not-well-resolved peaks at (110) and (200) planes can be ascribed to short range ordered 2D hexagonal pore array [45][46][47]. After the functionalization with PLA (Figure 3), the nanoparticles showed similar morphologies and sizes of bare NPs.…”
Section: Resultsmentioning
confidence: 97%
“…The XRD pattern, reported in Figure 2, showed a more defined peak related to the (100) diffraction plane and two broader and less intense peaks assigned to (110) and (200) planes usually attributed to 2D hexagonal pore array (P6 mm symmetry). The not-well-resolved peaks at (110) and (200) planes can be ascribed to short range ordered 2D hexagonal pore array [45][46][47]. After the functionalization with PLA (Figure 3), the nanoparticles showed similar morphologies and sizes of bare NPs.…”
Section: Resultsmentioning
confidence: 97%
“…The scattering vector, q , was calibrated using silver behenate. The 2D SAXS patterns were recorded with a 1M Pilatus detector with 981 × 1043 pixel resolution …”
Section: Methodsmentioning
confidence: 99%
“…For example, Abécassis et al observed the melting of lamellar micelles and the following formation of small micelles (<1 nm) in the synthesis of CdSe NPs using the combined in situ SAXS and WAXS . Yi et al used in situ SAXS to reveal the role of tetraethylorthosilicate/cetyltrimethylammonium bromide (TEOS/CTAB) micelles in the synthesis of mesoporous silica NPs …”
Section: Early Growth Stage (Stage Ii)mentioning
confidence: 99%